Pengaruh distribusi terhadap Ekonomi Islam - Imsar .; Restu Amelia Rambe (Jurnal Ekonomi dan Bisnis Digital, 2022)
This research is intended to determine the effect of economic development on human resources in Indonesia. This research uses a library study method (library research), which is a method of collecting data by understanding and studying theories from various literatures related to the research. Based on the results of the study showed that the influence of distribution on Islamic economics and vice versa and can be concluded that the economic distribution system in Indonesia still contains some weaknesses. This is due to the dominance of the market economic system (capitalist) which tends to have weaknesses, including inequality and social inequality, arising misalignment, profit maximization, materialism, moral crisis and welfare aside. The principle of distribution applied by the market economic system (capitalist) ultimately has an impact on the reality that the real rulers are the capitalists (capital owners and conglomerates). Therefore, it is natural that the policies issued by the government always favor the owners of capital or conglomerates and always sacrifice the interests of the people so that there is inequality (injustice) in the distribution of income and wealth.